2009
DOI: 10.1093/abbs/gmp009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of changes in endothelial cell-substrate adhesiveness during leukocyte adhesion by microelectrical impedance assay

Abstract: Adhesion of leukocytes to endothelial cells in inflammation processes leads to changes of endothelial cell-substrate adhesiveness, and understanding of such changes will provide us with important information of inflammation processes. In this study, we used a noninvasive biosensor system referred to as real-time cell electronic sensor (RT-CES) system to monitor the changes in endothelial cell-substrate adhesiveness induced by human monoblastic cell line U937 cell adhesion in a dynamic and quantitative manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Lipopolysaccharide treatment determined more intense staining in the perinuclear region in accordance with that observed by Iwakiri et al [19] and Zhang et al [20]. Additional investigation is necessary to clarify the functional significance of eNOS distribution after LPS treatment, taking into account the complex change in endothelial cell morphology induced by endotoxins [24,25]. …”
Section: Discussionsupporting
confidence: 80%
“…Lipopolysaccharide treatment determined more intense staining in the perinuclear region in accordance with that observed by Iwakiri et al [19] and Zhang et al [20]. Additional investigation is necessary to clarify the functional significance of eNOS distribution after LPS treatment, taking into account the complex change in endothelial cell morphology induced by endotoxins [24,25]. …”
Section: Discussionsupporting
confidence: 80%
“…The group of impedance-based instruments which cover the field of adherent cell surface measurements include several tools presently available in the market, with examples from Bionas and ACEA Biosciences (including the Roche xCELLigence System derived from ACEA), which monitors proliferation of adherent cells (53,54). These systems were recently summarized by Xi et al (55).…”
Section: Summary Of Impedance-based Cytometers Presently On the Marketmentioning
confidence: 99%
“…Compared with Coulter Counters (Z series, CASY), which usually measure the impedance signals using DC or low AC, microfluidic impedance flow cytometry (IFC) provides the possibility to perform impedance measurements at different frequencies covering a range of 100 kHz to 20 MHz. As already documented from various groups (18,51,52), it was shown that at such frequencies (starting from 1 MHz) other parameters (cellular membrane capacitance and cytoplasmic conductivity) can also be interrogated and provide additional information (besides number and size).The group of impedance-based instruments which cover the field of adherent cell surface measurements include several tools presently available in the market, with examples from Bionas and ACEA Biosciences (including the Roche xCELLigence System derived from ACEA), which monitors proliferation of adherent cells (53,54). These systems were recently summarized by Xi et al (55).…”
mentioning
confidence: 99%
“…It is a real-time cell analyzer that measures living cells without labeling. Electric impedance allows measurements of cellular processes such as proliferation, cytotoxicity, invasion, migration and cell viability (Atienza et al, 2006;Boyd et al, 2008;Ge et al, 2009) and give results comparable to imaging methods in some ways. Different staining methods have been developed that enable cells to absorb light.…”
Section: Why Digital Holographic Microscopy?mentioning
confidence: 99%